Quinoline‐Derived Two‐Photon‐Sensitive Octupolar Probes. Issue 5 (20th July 2017) - Dunkel, Petra; Petit, Morgane; Dhimane, Hamid; Blanchard‐Desce, Mireille; Ogden, David; Dalko, Peter I.
Abstract: A systematic study on quinoline‐derived light sensitive probes, having third‐order rotational symmetry is presented. The electronically linked octupolar structures show considerably improved linear and nonlinear photophysical properties under one‐ and two‐photon irradiation conditions compared to the corresponding monomers. Photolysis of the three acetate derivatives shows strong structure dependency: whereas irradiation of the 6‐ and 7‐aminoquinoline derivatives resulted in fast intramolecular cyclization and only trace amounts of fragmentation products, the 8‐aminoquinoline derivative afforded clean and selective photolysis, with a sequential release of their acetate groups ( δ u [730] =0.67 GM). Abstract : Let out of the cage : The incorporation of third‐order rotational symmetry into quinoline‐derived light‐sensitive probes results in improved linear and nonlinear photophysical properties compared to the corresponding monomers. The two‐photon uncaging cross‐section is unaffected.